Anatomy for dental medicine - Baker, Eric W. (Eric William) 1961-; Schünke, Michael; Schulte, Erik; Schumacher, Udo; Voll, Markus; Wesker, Karl (Thieme, 2015)
Anatomy for Dental Medicine, Second Edition , combines award-winning, full-color illustrations, explanatory text, and summary tables to guide the reader through the complex anatomy of the head and neck. Each region is arranged in a user-friendly format beginning with the skeletal framework. The musculature is then added, followed by the neurovasculature, and finally, topographic anatomy shows all structures in situ.